The research of microbiota on the territory of waste tailing of kara-balta (Eurasian Journal of Ecology, 2016)
Chemical and physical indexes of Kara-Balta uranium tailing soils were detected. Microbial community in this territory have passed through changes during last 50 years. The level of heavy metals reduced in selitabe zone. In the first and third horizonts the samples of soil with higher concentration of carbon, humus, nitrogen as indicators of microbial activity were determined. In addition the higher concentration of heavy metals are detected in these samples which may be the result of metabolism.
Keywords: microorganisms; uranium tailing of Kara-Balta; metagenomic analysis; heavy metals; humus of soil samples.